Effect of Knowledge/Practice of COVID-19 Prevention Measures on Return-to-Work Concerns; Attitudes About the Efficacy of Traditional Chinese Medicine: Survey on Supermarket Staff in Huanggang, China - Li, Lingru; Meng, Yue; Wang, Ji; Zhang, Ying; Zeng, Yong; Xiao, Huiqun; He, Jiangming; Liu, Zhenquan; Hou, Shujuan; Li, Tianxing; Qin, Jingbo; Fang, Yini; et al. (Frontiers in Public Health, 2021)
This study investigated how knowledge and practice of COVID-19 prevention measures affected concerns about returning to work among supermarket staff. Attitudes about the ability of traditional Chinese medicine (TCM) to prevent COVID-19 were also assessed. A cross-sectional study was conducted in Huanggang, Hubei Province, China,April23–25, 2020. From 2309 valid questionnaires, 61.5% of participants were concerned about resuming work; major concerns included asymptomatic infection (85.01%) and employees gathering in the workplace(78.96%). Multivariate logistic regression indicated that female gender, having school-aged children, and pregnancy were risk factors for being concerned about resuming work while good knowledge and practice of preventive measures were protective factors. Knowledge and practice of preventive measures were positively correlated. Among preventive measures, the highest percentage of participants knew about wearing masks and washing hands. Meanwhile,65.8%of participants expressed confidence in TCM’s ability to prevent COVID-19; 74% and 51.3%thought there was a need and a strong need, respectively, for preventive TCM-based products. Among them, 71.5% preferred oral granules. Regarding TCM as a COVID-19 preventative, most were interested in information about safety and efficacy. These findings suggest that promoting knowledge and practices regarding COVID-19preventioncan help alleviate concerns about returning to work. Meanwhile, TCM can feasibly be accepted to diversify COVID-19prevention methods. The trial is registered with the Chinese Clinical Trial Registry (ChiCTR2000031955) (http://www.chictr.org.cn/)